NUMERICAL METHODS OF SOLUTION OF BOUNDARY-VALUE PROBLEM FOR DIFFERENTIAL-ALGEBRAIC EQUATIONS OF THE SECOND ORDER - Mikhail Valeryanovich Buiaun; Nicolai Petrovich Rakhvalov; Tạ Duy Phượng (Tạp chí Khoa học Đại học Đà Lạt)
In this paper, some numerical methods for solving differential-algebraic equations of the second order are considered. We give conditions under which the algorithms are stable and converge to the exact solution of the original problem. Numerical examples are given.